2016
DOI: 10.1111/and.12693
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia impairs erectile function in rats by causing cavernosal fibrosis

Abstract: Men with hyperlipidemia are more likely to have erectile dysfunction (ED) than those without hyperlipidemia, but the mechanisms are not fully understood. The aim of this study was to investigate the underlying mechanism of ED caused by hyperlipidemia. Fourteen 8-week-old Sprague-Dawley rats were randomly divided into two groups: a control group and a hyperlipidemia group (fed chow containing 4% cholesterol and 1% cholic acid). After 6 months, we assessed erectile function by performing cavernous nerve electros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…Overactivated OS could impair erectile function through induction of penile functional cells apoptosis under many conditions including aging, hyperlipidemia, and DM [9,23,24]. Our data verified the inhibitory effect of hKLK1 on cells apoptosis through detection of endothelium, smooth muscle contents, and apoptotic percentage in tissue slides and further elucidated the mechanisms of reducing over expressions of Caspase3, cleaved Caspase3, and elevated ratio of Bax/Bcl-2.…”
Section: Discussionsupporting
confidence: 76%
“…Overactivated OS could impair erectile function through induction of penile functional cells apoptosis under many conditions including aging, hyperlipidemia, and DM [9,23,24]. Our data verified the inhibitory effect of hKLK1 on cells apoptosis through detection of endothelium, smooth muscle contents, and apoptotic percentage in tissue slides and further elucidated the mechanisms of reducing over expressions of Caspase3, cleaved Caspase3, and elevated ratio of Bax/Bcl-2.…”
Section: Discussionsupporting
confidence: 76%
“…The decrease of CC SMCs content, excessive collagen deposition, and a corresponding decreased ratio of smooth muscle to collagen in the CC were all associated with age-related ED in both human and rat 4243. Moreover, fibrosis, emerged as the predominant underlying cause of ED, is also evident in various rat models, including diabetes, hyperlipidemia, and androgen deficiency 444546. Our study found the decrease of CC SMCs, the excessive collagen deposition, and a corresponding decrease in the ratio of SMC to collagen in the CC of rats with HHcy.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al showed that castration leads to ED and induced CC fibrosis by suppressing autophagy and enhancing apoptosis in rats CSMCs (Wang et al, 2015). Li et al demonstrated that autophagy is inhibited in a hyperlipidemia rat ED model, which was considered to be part of the pathogenic mechanism (Li et al, 2017). In contrast, in the diabetic rat ED model, autophagy was overactivated, and icarisid II improved erectile function partially by reducing autophagy levels (Zhang et al, 2013a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al have demonstrated that aging critically affects erectile function and structure of penile tissues in rats, and reduces levels of telomerase and tankyrase 1 (Zhang et al, 2010). Li et al demonstrated that autophagy is inhibited in a hyperlipidemia rat ED model, which was considered to be part of the pathogenic mechanism (Li et al, 2017). In addition, tankyrase 1 might induce autophagy by regulating the mTOR signaling Figure 3 Immunohistochemistry and western blotting analysis of the PI3K/AKT/mTOR pathway.…”
Section: Figurementioning
confidence: 99%